Helicobacter pylori Infection and Its Associated Factors in Tripoli, Libya: Realities and Challenges - Nureddin Musa,; Salem Ateeg, (AlQalam Journal of Medical and Applied Sciences, 2026)
Helicobacter pylori infection is the main cause of chronic stomach inflammation and the main factor causing stomach ulcers and stomach cancer, affecting approximately half of the world's population. To identify factors associated with H. pylori infection in patients attending various government Hospitals in Tripoli for diagnosis and treatment. A cross-sectional analytical study was conducted from April 2025 to August 2025. 72 patients were infected with Helicobacter pylori, 58% of whom were female and 42% male. H. pylori infection to be 19.4% in the 31-40 age group and lowest in the 81-90 age group at 1.3%. Forty-six percent of patients had a university degree. 68% of H. pylori infections were found in people who used a source of untreated drinking water in compared with 32% use bottled water, and people who regularly ate at public restaurants had a slightly higher infection rate 56% compared to those who mainly ate at home. 72% of those who drink stimulants are infected, 74% of patients are smokers and infected, 26% non-smokers and infected too, 60% of patients who use traditional toilets are infected, 25% of patients have undergone histopathology examination, and 24% have undergone stool antigen and testing for Helicobacter pylori infection. Health awareness and educating the public about the risk factors associated with H. pylori infection and taking the necessary measures for a safe life are important factors in reducing this risk to public health. Further studies should be conducted to identify risk factors and develop a comprehensive strategic plan to combat them.